1984
DOI: 10.1002/ana.410160720
|View full text |Cite
|
Sign up to set email alerts
|

Ionic and acid-base regulation of neurons and glia during seizures

Abstract: Much evidence shows that glia regulates the cation and anion content of brain interstitial space. In rats the pH and bicarbonate (HCO3-) concentration of neurons and glia were derived from carbon 14-labeled HCO3- and dimethyloxazolidinedione uptake into brain and cerebrospinal fluid. Acetazolamide increases the total CO2 concentration in neurons and decreases the pH and HCO3- concentration in glia. Inhibition of glial carbonic anhydrase (CA) reduces conversion of neuronally derived CO2 to HCO3-, glial pH is lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 15 publications
4
24
0
Order By: Relevance
“…This enzyme relies mostly on metabolic substrates that are generated during neuronal activity, and directly regulates the intracellular C1' content in neuroglia through a Na+/K'-dependent adenosine triphosphatase (ATPase) anion exchanger that swaps extracellular C1-for intracellular HCO,- (74).…”
Section: Acetazolamidementioning
confidence: 99%
“…This enzyme relies mostly on metabolic substrates that are generated during neuronal activity, and directly regulates the intracellular C1' content in neuroglia through a Na+/K'-dependent adenosine triphosphatase (ATPase) anion exchanger that swaps extracellular C1-for intracellular HCO,- (74).…”
Section: Acetazolamidementioning
confidence: 99%
“…Central nervous system (CNS) seizures are characterised by repeated synchronised neuronal bursts, a subsequent increase in transmitter release, and changes in volume transmission and in the diffusion parameters of the extracellular space (1)(2)(3)(4). Electric activity and intercellular flow of ions and small molecules are regulated in part by gap junctions (GJs) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Woodbury [2] and Woodbury et al [3] have reported that SCAIs lower bicarbonate concentrations in astro cytes and thus, in the presence of SCAIs, pyruvate car boxylase may be substrate-limited. To determine the sensitivity of pyruvate carboxylase to substrate limita tion by low pyruvate, experiments were carried out with varied pyruvate concentrations.…”
Section: Effect Of Pyruvate and Acetoacetatementioning
confidence: 99%
“…We report that SCAIs, presumably by lowering astrocyte bicarbonate concentration [2,3], sec ondarily inhibit pyruvate carboxylase. There are seven mammalian isozymes of CA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation